Outcomes of nonsteroidal anti‐inflammatory drug toxicosis treated with therapeutic plasma exchange in 62 dogs. (5th August 2022) - Butty, Emmanuelle M.; Suter, Steven E.; Chalifoux, Nolan V.; Lynch, Alex M.; Mauro, Katie D.; Moyle, Rachel B.; Ehrhardt, Caryn M.; Robertson, James B.; Culler, Christine A.; Londoño, Leonel A.; Vigani, Alessio; Ueda, Yu; et al.
Abstract: Background: Therapeutic plasma exchange (TPE) is gaining popularity for the management of nonsteroidal anti‐inflammatory drug (NSAID) overdose in dogs. Hypothesis/Objectives: Describe a population of dogs treated with TPE for NSAID overdose. Animals: Sixty‐two dogs with NSAID overdose treated with TPE. Methods: Multicenter retrospective study of dogs treated with TPE for ibuprofen, carprofen, or naproxen overdose. Results: The median dose of ibuprofen, carprofen or naproxen ingested was 533 mg/kg (range, 36‐4857 mg/kg), 217 mg/kg (range, 88‐625 mg/kg) and 138 mg/kg (range, 26‐3000 mg/kg), respectively. Based on previously established toxic ranges for each NSAID, 2 (3.2%), 14 (22.6%), and 46 (74.2%) dogs ingested a gastrointestinal, renal, and neurological toxic dose, respectively. The median time between ingestion and presentation was 4 hours (range, 1‐20 hours). The median number of plasma volumes processed was 1.6 (range, 0.4‐2.2). The median TPE session duration was 2 hours (range, 1‐4.5 hours). Circuit clotting developed during 8 (12.9%) sessions. Patient adverse events reported during 21 (33.8%) sessions consisted of urticaria (12.9%), asymptomatic hypocalcemia (9.6%), and hypotension (9.6%). The median duration of hospitalization was 2.25 days (range, 1‐11 days). Sixty‐one (98.4%) dogs survived to discharge, and none were rehospitalized. Thirty‐one (91.1%) of the 34 dogs with at least 1 follow‐up visit were not azotemic at the time of reevaluation. Conclusions and Clinical Importance: This population of dogs managed with TPE had excellent outcomes, even in cases of high NSAID dose ingestion. When TPE is available and the time frame is appropriate, this extracorporeal modality should be considered for the management of NSAID overdose.